Exponential Stability of Viscoelastic Structure with Second Sound - C. Gorain, Ganesh; Carlos; Vera, Octavio; Ram, Srikanta (Electronic Journal of Applied Mathematics, 2024)
This manuscript deals with a thermo-viscoelastic system describing the vibrations of a flexible structure. We study this structure's stabilization problem when subjected to Kelvin-Voigt damping and the second sound. Cattaneo-Vernotte's law governs the thermal effect, eliminating the physical paradox of equal speed of waves in the classical thermoelastic theory. Semigroup theory proves the solution's existence and uniqueness. Exponential stability is proved by the energy method.